2018
DOI: 10.1186/s12967-018-1703-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of surgical paraaortic staging in locally advanced cervical cancer: a multicenter cohort analysis from the FRANCOGYN study group

Abstract: BackgroundThe prognostic impact of surgical paraaortic staging remains unclear in patients with locally advanced cervical cancer (LACC). The objective of our study was to evaluate the survival impact of surgical staging in patients with LACC and no evidence of paraaortic lymph node (PALN) metastasis on pre-operative imaging work-up.MethodsData of 1447 patients with cervical cancer treated between 1996 and 2016 were extracted from maintained databases of 10 French University hospitals. Patients with locally adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…Analyzing the data of GOG 85, GOG 120, and GOG 165 trials, Gold et al showed a benefit in progression-free survival (50% vs 36%) and overall survival (54% vs 40%) in favor of surgical staging, which was more beneficial for stage III/IV than for stage II. 7 Dabi et al 10 compared 377 patients who underwent surgical staging with 270 patients who had clinical staging. After a mean follow-up of 38 months, patients in the surgical group had a better prognosis with respect to disease-free survival (OR 0.64) and overall survival (OR 0.43).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the data of GOG 85, GOG 120, and GOG 165 trials, Gold et al showed a benefit in progression-free survival (50% vs 36%) and overall survival (54% vs 40%) in favor of surgical staging, which was more beneficial for stage III/IV than for stage II. 7 Dabi et al 10 compared 377 patients who underwent surgical staging with 270 patients who had clinical staging. After a mean follow-up of 38 months, patients in the surgical group had a better prognosis with respect to disease-free survival (OR 0.64) and overall survival (OR 0.43).…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that para-aortic surgical staging contributes significantly to individualise the radiation treatment plan especially in patients with positive pelvic uptake [ 35 ]. FRANCOGYN study including 647 patients with LACC treated by concurrent chemoradiation therapy (CRT) and no evidence of para-aortic metastasis on pre-operative imaging work-up, confirmed in multivariate model analysis surgical staging as an independent prognostic factor for Disease Free Survival [ 36 ]. On the other hand, a retrospective study from Mayo Clinic registry including 148 patients did not find differences comparing surgical versus radiological staging (mainly based on CT, MRI and PET combination) in 5-year PFS (HR 1.11, 95% CI 0.54–2.30, p = 0.77) and 5-year OS (HR 1.02, 95% CI 0.46–2.29, p = 0.96).…”
Section: Discussionmentioning
confidence: 99%
“…One of the questions to be answered is the worth of performing a radical lymphadenectomy or a simply sampling, which we call suboptimal lymphadenectomy. Some authors reported a survival benefit in salvage and radical aortic lymphadenectomy either in recurrence or in surgical staging with negative imaging preoperative test [ 21 22 ]. In that line, our data demonstrate that a radical lymphadenectomy up to the renal vein improves both DFS and OS.…”
Section: Discussionmentioning
confidence: 99%